2019
DOI: 10.1128/iai.00227-19
|View full text |Cite
|
Sign up to set email alerts
|

Intradermal Synthetic DNA Vaccination Generates Leishmania -Specific T Cells in the Skin and Protection against Leishmania major

Abstract: Vaccination remains one of the greatest medical breakthroughs in human history and has resulted in the near eradication of many formerly lethal diseases in many countries, including the complete eradication of smallpox. However, there remain a number of diseases for which there are no or only partially effective vaccines. There are numerous hurdles in vaccine development, of which knowing the appropriate immune response to target is one of them. Recently, tissue-resident T cells have been shown to mediate high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…This trend can be seen in this study with a MERS DNA vaccine (Figure 1), as well as in recent clinical studies of DNA vaccines targeting HIV (11) and Ebola (10). In addition, it could be that there is a different induction of T cell trafficking induced by ID vs IM immunization such as has recently been reported in a leishmania model system (22). One hypothesis is that different cell populations are transfected between the muscle (myocytes) and skin (keratinocytes, fibroblasts, dendritic-like cells, adipocytes, and potentially some myocytes)(23), resulting in different recruitment profiles for antigen presenting cells to the site of immunization.…”
Section: Discussionsupporting
confidence: 84%
“…This trend can be seen in this study with a MERS DNA vaccine (Figure 1), as well as in recent clinical studies of DNA vaccines targeting HIV (11) and Ebola (10). In addition, it could be that there is a different induction of T cell trafficking induced by ID vs IM immunization such as has recently been reported in a leishmania model system (22). One hypothesis is that different cell populations are transfected between the muscle (myocytes) and skin (keratinocytes, fibroblasts, dendritic-like cells, adipocytes, and potentially some myocytes)(23), resulting in different recruitment profiles for antigen presenting cells to the site of immunization.…”
Section: Discussionsupporting
confidence: 84%
“…Most importantly, Tsrm cells contribute to localized protection against re-infection with cutaneous pathogens (4)(5)(6)(7)(8)(9). In addition, Trm cell development has been tracked in mice following vaccination and was positively correlated with vaccination efficacy (10)(11)(12)(13), making Trm cells a promising target for vaccination (14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Lumena et al showed that mice immunized intradermally with PEPCK were superior in generating skin-resident PEPCK-specific T cells when compared to mice immunized intramuscularly. They further observed that when challenged with Leishmania major parasites, intradermal immunization led to significant protection, which was not observed after intramuscular immunization [106].…”
Section: Advances In Vaccination Against Leishmaniasismentioning
confidence: 98%